A Thermodynamic Method for the Estimation of Free Gas Proportion in Depressurization Production of Natural Gas Hydrate - Li, Shouding; Sun, Yiming; Lu, Cheng; Chen, Weichang; Liu, Shimin; Chen, Lin; Li, Xiao (Frontiers in Earth Science, 2022)
Free gas saturation is one of the key factors that affect the overall production behaviors of hydrate reservoirs. For example, different free gas contents could alter the thermal response of hydrate reservoir to the artificial stimulation and hence change the gas production performance. To investigate whether and how much the hydrate reservoir contains free gas, we proposed a thermodynamic method to calculate the total heat consumption of hydrate dissociation throughout gas production and assess the free gas proportion. Based on the monitoring data of the first offshore hydrate production in Japan, we calculated the total heat consumption and analyzed the contributions of heat convection, heat conduction, and sensible heat during the entire test. The calculation results showed that there is likely to be a certain amount of free gas in the hydrate reservoir in Eastern Nankai Trough. In addition, the analysis of different heat sources revealed the critical thermodynamic phenomenon that the reservoir sensible heat was the main source for enthalpy of hydrate dissociation, which consistently contributed more than 95% of the total heat supply during the 6-day production test. The results of this work may help upgrade the production strategy for natural gas hydrates.